Aspects of the biology and population dynamics of the geelbek Atractoscion aequidens (Cuvier) (Pisces: Sciaenidae) off the South African coast - Griffiths, Marc H (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1988)
The geelbek Atractoscion aeguidens is an important commercial and recreational linefish species along the South African eastern seaboard . Aspects of its biology and population dynamics were investigated using data collected from various sampling sites along the South African east coast and from catch statistics obtained from both the Sea Fisheries Research Institute (Cape Town), and dealer records. The biological aspects studied included age and growth, reproduction and feeding. It was established that A. aeguidens is a fast growing species with a relatively late age at sexual maturity and a 1:1 sex ratio. Feeding studies revealed that it has become specialized to feed on small pelagic fish. The South African geelbek stock consists of three distinct age related sub-populations, each representing a particular phase in the life cycle. The sub-adults (1-4 yrs) occur in the South West Cape and feed predominantly on anchovy, Engraulis capensis, which they follow, moving inshore in summer and offshore in winter. The adults (5-9 yrs) undergo a seasonal inshore migration to Natal where they spawn in spring. The dynamics of this migration are strongly influenced by the annual movement of their principal prey viz. , Sardinops ocellatus, to that region. As a result the geelbek first arrive in Natal during mid winter. Evidence is also presented to suggest that a significant number of "adolescent " fish (4-5 yrs) undergo limited gonad maturation and a partial migration to at least as far as the South East Cape. Spawning appears to occur offshore. It is postulated that eggs and larvae are transported southwards by the peripheral waters of the Agulhas Current. After spawning the adults probably remain offshore and use the current to aid their return to the South and South West Cape, where they spend summer feeding on the Agulhas Bank. Juveniles (<1 yr) first appear in the South East Cape between January and March. They apparently use this region as a nursery area for almost a year before moving southwards to join the sub-adults in the South West Cape. In the South East Cape, the juveniles feed initially on mysids whereafter they switch to anchovies and pilchards. A preliminary stock assessment using yield per recruit and spawner biomass per recruit models, indicated that despite the current legislation the South African geelbek population is already overexploited. This is largely attributed to high rates of fishing mortality of the migratory adult population. Further management recommendations are therefore proposed. These include a size limit (660 mm FL), derived from an investigation of the interrelationship between natural mortality and somatic growth in a theoretical unexploited cohort, as well as a uniform bag limit for all user groups (5 fish per person per day)
Keywords: Sciaenidae -- South Africa; Fish populations -- South Africa; Atractoscion; Atractoscion -- South Africa -- Ecology; Atractoscion -- South Africa -- Physiology